Examining the Role of P3H: Motivations, Barriers, and Strategies Behind Halal Certification of Food Micro, Small, and Medium Enterprises - Teti Indrawati; Fariz Al-Hasni (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
Law Number 33 of 2014 concerning Halal Product Assurance requires halal certification for products circulating in Indonesia, and the government provides a Free Halal Certification (SEHATI) scheme based on self-declaration by business actors specifically for Micro and Small Enterprises (MSEs). In its implementation, Halal Product Process Facilitators (P3H) act as the spearhead that bridges state policies with business actors in the field. This study aims to analyze the motivations, obstacles, strategies, and expectations of P3H under the auspices of the Halal Center UIN Mataram in realizing legal compliance of MSEs for food products. The study uses a qualitative juridical-empirical approach through interviews, observations, and documentation of 26 P3Hs in ten districts/cities in West Nusa Tenggara Province, which are analyzed using the interactive model of Miles and Huberman and tested for validity through source triangulation. The results of the study indicate that P3H motivation is dominated by religious-social and self-development drives; obstacles faced include geographical constraints, limited infrastructure, low legal awareness of business actors, and unscheduled honorariums; Meanwhile, the adaptive strategies adopted include intensive outreach and virtual mentoring. P3H's hopes are focused on accelerating the process, increasing honorariums, and providing regular coaching.